FAKTOR-FAKTOR RISIKO FISKAL DALAM PENGANGGARAN DAERAH (Studi pada Pemerintahan Aceh) - Jalaluddin, Jalaluddin (Jurnal Mentari, 2010)
This research was conducted with the objective of identifying risk actors in fiscal budgeting of the Government of Aceh. Theoretically, the results of this study are expected to provide inputs for the Government of Aceh to be able to do things that help to reduce fiscal risks in the Aceh government budgeting. The data used were obtained through field research through the deployment of a questionnaire to measure attitudes, opinions, and perceptions of a person or group of persons of a particular social phenomenon, which has been specifically defined by the researchers. The population in this study was all officials involved in financial processes, both constituting (SKPA) and the budget approval board (DPRA). The test results produced 11 (eleven) factor reduced from 32 items and has a value of variable loading ≥ 0.5 which consists of four sources of risk of regulatory factors and mechanisms in the budgeting area, namely: with KUA and budget documents synchronization factors, factors of risk management in government area, changes in regulatory systems of budgeting and fiscal stress associated with the consideration of budget surpluses and deficits; three sources of risk from political factors in the budgeting area, there are: superiority of power factor (discretionary power) and the opportunistic behavior of individual legislators as well as factors executive and legislative relations (related mechanism formulation and discussion of budget); and four sources of risk factors of opportunistic behavior and moral hazard in budgeting, consisted of opportunistic behavior of individual in formulating the budget, a factor of moral hazard and the proposed budget planners, management public organizations factor related to clarity of responsibility, authority and functions as well as the potential for fraud in the budgeting process. Keywords: factors, regulation and mechanisms, politics, opportunistic behavior,  moral hazard, budgeting     DAFTAR  PUSTAKA Abdullah, Syukriy, dan Jhon Andra Asmara, (2006). “Perilaku Oportunistik Legeslatif Dalam Penganggaran Daerah: Bukti Empiris Atas Aplikasi Agensi Theory di Sektor Publik”. Diakses dari http://swamandiri.org/2008/02/10.   Baswir, Revrisond (2000) Akuntansi Pemerintahan Indonesia. Edisi Ketiga. Yogyakarta: BPFE. Blondal, (2008). Fiscal Risk Management, IMF High-Level Seminar on Fiscal Risk Management, Paris, 28 October 2008. Diakses dari http://blog-pfm.imf.   Brixi, Hana Polackova dan Allen Schick, (2002), Government at Risk:Contingent Liabilities and Fiscal Risk, dalam Brixi andSchick (ed), 2002. Governmentat Risk: Contingent Liabilities and Fiscal Risk, a Copublication of The World Bank and Offord University Press. Hal: 1-58.   Brixi, Hana Polackova dan Ashoko Moody, (2002). Dealing With Government Fiscal Risk: an Overview dalam Brixi danSchick (ed), 2002. Government at Risk: Contingent Liabilities and Fiscal Risk, a Copublication of The World Bank and Offord University  Press. Hal: 21-58.   Ghozali, Imam, (2007). Aplikasi Analisis Multivariate dengan Program SPSS, Badan Penerbit Universitas Diponegoro, Semarang.   Halim, Abdulah, (2008). Hubungan dan Masalah Keagenan di Pemerintahan Daerah: Sebuah Peluang Penelitian Anggaran dan Akuntansi. Diakses dari http://www.bppk.depkeu.go.id.   Hemming, Richard dan Murray Petrie, (2002). A Framework for Assesing Fiscal Vulnerability, dalam Government at Risk, dalam Brixi dan Schick (ed), 2002. Government at Risk: Contingent Liabilities and Fiscal Risk, a Copublication of The World Bank and Offord University Press. Hal: 159-178. Hair, Joseph F. Rolph E. Anderson, Ronal L. Tatham and William C. Black, 1998, Multivariate Data Analysis, Fith Edition, Prentice Hall Upper Saddle River New Jersey 07548.   International Monetary Funds (IMF), (2007). Increasing Fiscal Transparency-Brazil´s Budgetary Fiscal Risk Report. Diakses dari http://blogpfm.imforg/pfmblog/2007/11/increasing-fisc.html Mardiasmo  (2005). Akuntansi Sektor Publik. Yogyakarta: Penerbit Andi   Ma, Jun (2002), Monitoring Fiskal Risk of Subnational Goverment: Selected Country Experiences dalam Brixi dan Shick (ed), 2002. Government at Risk: Contingent Liabilities and Fiskal Risk, a Copublication of The World Bank and Offord University press. Hal 59-78   Pemerintah Republik Indonesia, (2006). Peraturan Menteri Dalam Negeri No.13 Tahun 2006 tentang Pedoman Pengelolaan Keuangan Daerah.   Romarina, Arina dan ahmad Maqfatih (2010). Faktor-Faktor Risko Fiskal dalam Penganggaran Daerah, Jurnal BPPK vol 1 Schick, Allen, (2002). Budgeting for fiscal Risk dalam Brixi dan Schick (ed), 2002. Government at Risk: Contingent Liabilities and Fiscal Risk, a Copublication of The World Bank and Offord University Press. Hal: 79-97. --------- (2008). Budgeting for Fiscal Risk, Slide Presented to the Fiscal Affairs Division International Monetary Funds, 17 September 2008. Diakses dari http://blogpfm.imf.org/pfmblog/ files/ budgeting_for_fiscalrisk byshick.ppt   Sugiyono, (2008). Metode Penelitian Bisnis, Alfabeta, Bandung.   Sekaran, Uma (2006). Metodologi Penelitian Untuk Bisnis. Jakarta : Salemba Empat www.serambinews.com, diakses 21 Maret 2011